ALLERGIC ENCEPHALOMYELITIS IN MONKEYS IN RESPONSE TO INJECTION OF NORMAL MONKEY NERVOUS TISSUE - Morgan, Isabel M. (The Rockefeller University Press, 1947)
By subcutaneous injection of central nervous tissue emulsified with adjuvants according to Freund's technique it has been possible to induce in the majority of monkeys an acute disseminated encephalomyelitis which is interpreted as an isoimmunization to CNS tissue. Positive reactions occurred only in response to CNS tissue containing white matter; i.e., cerebral white matter, spinal cord (whether normal or poliomyelitis-infected), and cortical "gray" matter (with an estimated 10 per cent contamination with white matter). No reaction occurred when peripheral nerve or kidney suspension or saline alone was injected with adjuvants. The perivascular and extravascular infiltration induced was confined to the CNS.